School Leadership Practices and Administrative Experiences in the Implementation of the School-Based Feeding Program: A Qualitative Study in the Reina Mercedes District, Schools Division of Isabela - Apostol, Giselle Ann; Paragas, Benjamin (Studies in Technology and Education, 2026)
This qualitative study explored school leadership practices and administrative experiences in the implementation of the School-Based Feeding Program (SBFP) in the Reina Mercedes District, Schools Division of Isabela. The study aimed to examine how school leaders manage, supervise, and sustain the implementation of the feeding program, including the challenges and support mechanisms encountered during program implementation. Using a descriptive qualitative research design, data were gathered through semi-structured interviews, focus group discussions, document analysis, and field observations involving school heads, feeding coordinators, and selected teachers. Thematic analysis revealed four major themes: (1) collaborative and participatory leadership practices in feeding program implementation, (2) adaptive administrative management and resource mobilization, (3) learner welfare and community-centered program support, and (4) operational and administrative challenges in sustaining the School-Based Feeding Program. Findings showed that school leaders demonstrated strong commitment, collaboration, and instructional leadership in ensuring effective feeding program implementation through stakeholder coordination, resource management, monitoring systems, and community partnerships. The program positively contributed to learner participation, attendance, and nutritional support. However, logistical limitations, resource constraints, procurement concerns, and administrative workload affected implementation efficiency. The study concludes that collaborative leadership and adaptive administrative practices significantly contribute to the sustainability and effectiveness of school-based feeding programs. Strengthening institutional support, stakeholder collaboration, and administrative capacity-building programs is recommended to improve feeding program implementation in public elementary schools.